Everyday lives of middle-aged persons living with multimorbidity: protocol of a mixed-methods systematic review - Marjan Van Den Akker; Mirjam Dieckelmann; Ana Isabel González-González; Julia Nothacker; Maria-Sophie Brueckle; Beate S Müller; Truc Sophia Dinh; Robin Brünn (BMJ Open)
Introduction Multimorbidity is the simultaneous occurrence of several (chronic) diseases. Persons living with multimorbidity not only have complex care needs, but the burden of care often has a negative impact on their family lives, leisure time and professional activities. The aim of this project is to systematically review the literature to assess how multimorbidity affects the everyday lives of middle-aged persons, and to find out what abilities and resources help in the development of coping strategies to overcome the challenges of living with it.Methods and analysis We will systematically search for studies reporting on the everyday life experiences of middle-aged persons (30–60 years) with multimorbidity (≥2 chronic conditions) in MEDLINE, CINAHL, PsycINFO, Social Sciences Citation Index, Social Sciences Citation Index Expanded, PSYNDEX and The Cochrane Library from inception. We will include all primary studies that use quantitative, qualitative and mixed methodologies, irrespective of publication date/study setting.Two independent reviewers will screen titles/abstracts/full texts, extract data from the selected studies and present evidence in terms of study/population characteristics, data collection method and the phenomenon of interest, that is, everyday life experiences of middle-aged persons with multimorbidity. Risk of bias will be independently assessed by two reviewers using the Mixed Methods Appraisal Tool. We will use a convergent integrated approach on qualitative/quantitative studies, whereby information will be synthesised narratively and, if possible, quantitatively.Ethics and dissemination Ethical approval is not required due to the nature of the proposed systematic review. Results from this research will be disseminated at relevant (inter)national conferences and via publication in peer-reviewed journals.PROSPERO registration number CRD42021226699.